Dual-hormone regulation of psychopathy: Evidence from mass spectrometry. (January 2019) - Roy, Ashlin R. K.; Cook, Terence; Carré, Justin M.; Welker, Keith M.
Highlights: Replication attempt of testosterone and cortisol interaction with psychopathy. Mixed evidence of dual-hormone hypothesis reversals. Sample 1 fails to replicate dual-hormone interaction in men using ELISAs. Sample 2 supports dual-hormone hypothesis across mixed gendered sample. Sample 2 uses a more precise assay methodology (mass spectrometry). Abstract: Previous work suggests that testosterone and cortisol interactively predict psychopathy. This effect represents a reversal of the established dual-hormone hypothesis, whereby testosterone is positively correlated with psychopathic traits, but only among individuals with elevated cortisol concentrations. This study aims to replicate the dual-hormone moderation of psychopathy in two independent samples. Enzyme-linked immunoassays (ELISAs) were used to assess cortisol across both samples and testosterone in Sample 1 ( n  = 165, 100% males). To address recent criticism of ELISAs and potentially extend these findings to women, testosterone concentrations were determined by liquid chromatography tandem mass spectrometry (LC–MS/MS) in Sample 2 ( n = 213, 44.1% males). We found conflicting evidence of the dual-hormone moderation of psychopathic traits. Although results were non-significant in Sample 1, a reversal of the dual-hormone hypothesis was found in Sample 2, in which testosterone was positively correlated with psychopathic traits, but only among individuals with high cortisol. This replication provides mixed support for less common reversals to the dual-hormone hypothesis. These findings emphasize the importance of using LC–MS/MS to measure testosterone and adds to the growing body of work on the relationship between hormones and psychopathology in general.